Cognitive Discourse Analysis of Metaphor in Dhain’s 2020 Drama “Flower and Knife” - Abbood, Ansam Ghazi; Jamel, Heevi Khaled; Gargary, Khalid Ilias Basheer (Jurnal Simki Pedagogia, 2024)
This paper presents a critical analysis of “FLOWER AND KNIFE” by Ahmed Yasir Dhain. It was written in 2020. The play represents two couple of notions “love and hate” “flower and knife". Those notions are represented by the number of characters who reflect our views about life. The writer has shown contrastively those notions, which would be in contrastive till unknown time. The study is based on cognitive metaphor analysis, especially the conceptual metaphor. Since the analysis of conceptual metaphor has an important role in discovering the attended messages and the real meaning of the dramatic text through the mapping between the source domain and the target domain. It is also important to discover the ability of the writer to add some new concepts and change the existing ones. The study follows Kövecses' 2002 Conceptual Metaphor Model. It deals with the three types of cognitive metaphor, they are structural, orientational, and ontological. The study is qualitative, it attends to describe and analyze the data critically. It shows how different discourse structures can be critically analyzed by cognitive perceptions. The study aims to analyze the conceptual metaphor as a critical tool. It tries to discover the language's role in constructing concepts through using dramatic devices, especially conceptual metaphors. It aims to criticize the concepts of love, hate, flower, and knife and how they can influence our thoughts and construct new ones. It also aims to find out the connection between conceptual metaphor and critical discourse analysis. Based on the paper literature review and the result of data analysis, the study finds that the play is full of conceptual metaphor expressions which attend to a conceptual change. It shows that the conflict between love and hate is a conflict between man and woman in society. Women can be flowers and knives at the same time. The paper shows that the writer has used all the three types of conceptual metaphor in order to support the love purity which can destroy all hates. He wants to tell us that love can be a source of life.